Analysis of promising methods for protection of fruit trees generative organs from spring frosts - Рудницкая, Анна Викторовна (Technology audit and production reserves, 2015)
Analysis of the known methods and means of mechanization of frost protection was carried out. Schemes of the direction of flow of cold and warm air using various methods and means of mechanization were composed. It was proposed a classification of methods and means of mechanization of fruit trees protection from frost, which allows selecting a promising direction to enhance the process of protection of the generative organs of fruit trees from spring frosts. It was found that a promising direction is the development of the complex system which consists of temperature condition monitoring, protection technological process and mechanization means. Frost protection can be performed in several ways, by combining known methods. In such case, it is necessary to examine the type of frost. Addressing these problems helps to choose a promising direction of development of this sector of mechanization, as well as to expand the set of methods and means for the protection of the generative organs of fruit trees from spring frosts.